Ever-expanding university? Social and ethnic inequality in education - Jonsson, J (Oxford University Press, 2014)
Seen in a historical perspective, there has always been a tension between the view that higher education should be expanded, and the view that it should be kept to a limited group of outstanding talents. In many countries, there has been a massive change toward support for the expansionist view, most recently during the 1990s and onward, where politicians in England and Sweden have gone so far as to claim that at least half of a cohort should pursue tertiary-level education. It is likely that there are both ideological and prosaic reasons behind such goals.